An analysis of trends in maternal mortality at a tertiary care teaching hospital of Western Rajasthan, India: a four year retrospective study - Agrawal, Neha; Uppadhaya, Sandeep Kumar; Hakim, Afzal; Mittal, Manish (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal mortality reflects not only the adequacy of health care services of any country or state but also the standard of living and socio-economic status of the community. India is among those countries, which has a very high maternal mortality ratio; the state of Rajasthan having the third highest maternal mortality in the country. This study was done to assess the maternal mortality in a tertiary hospital situated in Jodhpur, a city in Western Rajasthan where large numbers of patients are referred from rural parts in and around the city. Methods: This study was done to assess the trends in maternal mortality at a tertiary medical college hospital situated in Western Rajasthan. A retrospective hospital based study was carried out in the Obstetrics and Gynaecology Department of Ummaid hospital, Dr S. N. Medical College situated in Jodhpur, Rajasthan, India over a period of 4 years from July 2010 to June 2014. Results: During the study period spanning 4 years, there were in total 84,746 live births with 195 maternal deaths. The mean maternal mortality ratio for the four year period was found to be 230.1 per lakh live births. Conclusions: The maternal mortality was quite high than the national average.